Implementation strategy of technology in optimizing the ijarah contract process in Islamic banks - Baiq Diana Putri; Romi Putra Saroji; Hermawati Hermawati (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
This article aims to explore technology implementation strategies in the Ijarah contract process at Islamic banks to enhance operational efficiency, Sharia compliance, and customer satisfaction. The research method employed is a qualitative approach through library research, involving the analysis of secondary data from scientific journals, books, research reports, and policy documents related to Islamic banking and technology. The analysis is conducted by categorizing information based on the type of technology and its impact on efficiency and Sharia compliance, as well as using descriptive and comparative approaches to identify relevant patterns and relationships. The research findings indicate that the application of technologies such as digital document management systems, electronic signatures, and online platforms can optimize the Ijarah contract process by reducing time and costs while improving transparency and accuracy. However, challenges such as resistance to change and high initial costs must be addressed through training, effective communication, and collaboration with technology providers who understand Sharia principles. This research contributes by offering technology implementation strategies that can strengthen the competitive advantage of Islamic banks in an increasingly digital market and provide in-depth insights for the development of Islamic banking theory and practice.